(untitled) (Journal of the Sylhet Agricultural University, 2025)
The existing rice-growing system continues to search for a biological way to decrease the harmful effects of using chemicals to control weeds. One way an allelopathic plant suppresses the plants around it is by releasing compounds that are also allelopathic, a process known as plant allelopathy. The current study examined the allelopathic effects of Eleocharis atropurpurea and Fimbristylis dichotoma on weed management of aman rice. It was carried out from July to December 2019 at the Bangladesh Agricultural University’s Agronomy Field Laboratory in Mymensingh. The field trial included five treatments such as A: Residues of E. Atropurpurea and F. Dichotoma; No crop residues (R1), 1.0 t ha-1 (R2), 2.0 t ha-1 (R3), 3.0 t ha-1 (R4), Farmars practices (R5) and three rice varieties such as BRRI dhan34 (V1), Nizershail (V2), and Kalozira (V3). In field experiment, the highest shama weed density (15.98) was found in BRRI dhan34 when no reside was applied and the lowest (2.38) was found in chesra at farmer’s practice. In case of dry weight, the highest value (12.35 g) was recorded at no residues for the variety of BRRI dhan34, whereas the lowest weed dry weight (1.38 g) was found in kalozira at farmer’s practice. Applying residues of Eleocharis atropurpurea and Fimbristylis dichotoma, especially at higher rates (3.0 t ha-1), is recommended for sustainable weed control in aman rice cultivation. J. Sylhet Agril. Univ. 11(1): 59-66, 2024